NARRATIVE REVIEW: LAPAROSCOPIC VS OPEN REPAIR OF INGUINAL HERNIAS IN ATHLETES: CLINICAL OUTCOMES AND RETURN TO SPORT - Natalia Krupa; Aleksandra Marzec; Dominika Galińska; Natalia Domańska; Anna Roman; Joanna Zajączkowska; Natalia Marzec; Małgorzata Cherek; Weronika Praska; Stanisław Wardęcki (International Journal of Innovative Technologies in Social Science, 2026)
Background: Inguinal hernias are super common, especially in active folks like athletes and gym-goers. They can really mess things up – causing pain, tanking your performance, and sidelining you from sports for weeks. If rest, physical therapy, or other conservative fixes don't cut it, surgery's usually the best bet to get you back in the game. There are two main surgical routes: open surgery (the classic approach) and laparoscopic surgery (the minimally invasive one). Both work well, but which one's right for you depends on factors like your hernia size, your activity level, and what your surgeon recommends. Goal: This narrative review compares laparoscopic and open inguinal hernia treatment in athletes, emphasizing clinical results, complications, and timetables for return to sport. Methods: A narrative literature review was performed using PubMed and Google Scholar. Studies were identified using combinations of relevant keywords, including “inguinal hernia”, “laparoscopic repair”, “open repair”, and “athletes”. Clinical studies, systematic reviews, and guidelines published primarily within the last 10 years were included. A qualitative synthesis was performed. Results: Available evidence suggests that laparoscopic repair may be associated with reduced postoperative pain and earlier functional recovery compared with open repair. Long-term outcomes, including recurrence rates, appear comparable between techniques. However, evidence specifically addressing athletic populations remains limited and heterogeneous. Conclusions: Both surgical techniques are effective and safe. Laparoscopic repair may offer advantages in early recovery and return to sport. Surgical decision-making should be individualized.